Suspension oxidative roasting for enhanced gold leaching from a quartz-rich refractory gold ore: Process optimization and microstructural evolution - Yan Song; Jianping Jin; Yanjun Li; Bing Zhao; Min Sun; Yuexin Han (Minerals Engineering, 2026)

Oxidation patterns and stability mechanisms of marine oils revealed by oxidized triglyceride and phospholipid analysis using RPLC–Q-TOF - Nan Meng; Yaru Li; Peixu Cong; Yu Song; Yanjun Liu; Jie Xu; Changhu Xue (Food Research International, 2026)

Enhanced peroxymonosulfate activation for antibiotic removal using Ni1Mn1Fe1-LDO/g-C3N4: Metallic electronic synergy and oxygen vacancy effects - Wenqi Bu; Zhan Wang; Tao Zhu; Zhaocai Wu; Siqi Liu; Jiang Li; Qianwen Wang; Shuaishuai Xin; Xiaozhe Song; Yanjun Xin; Qinghua Yan; Guocheng Liu (Environmental Research, 2026)

Model-based inference of monsoonal moisture from stalagmite and tree-ring δ18O - Qiang Li; Yifan Wu; Jiachuan Wang; Yu Liu; Yanjun Cai; Haiwei Zhang; Liangcheng Tan; Jingyao Zhao; Changfeng Sun; Huiming Song; Yang Xu; Yueer Li; et al. (Quaternary Science Reviews, 2026)

Long-term petroleum pollution alters soil microbial communities via electron transfer capacity: Evidence from a 35-year chronosequence - Chengze Yu; Mingxiao Li; Jun Cui; Yanjun Xin; Ran Song; Wangmi Chen; Jiaqi Hou; Jianbing Li; Huibin Du; Beidou Xi (Journal of Environmental Sciences, 2026)

Disrupting the cardiolipin oxidation-apoptosis axis: low-temperature, high-salinity depuration extends anhydrous storage in Pacific oysters - Nan Meng; Xinyu Cao; Yu Song; Peixu Cong; Yanjun Liu; Yi Liu; Changhu Xue; Jie Xu (Food Research International, 2026)

Mechanisms of Dissolved Organic Matter Migration in Coal Mining Subsidence Areas - Jing Xu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Yanjun Liu; Kai Zhang; Lin Wu; Xin Shu (Mine Water and the Environment, 2026)

Geochemical and hydrological controls on aragonite versus calcite precipitation in speleothems and paleoclimatic implications - Rui Zhang; Haiwei Zhang; Christoph Spötl; Carlos Pérez-Mejías; Zixin Guan; Heather Stoll; Yanjun Cai; Liangcheng Tan; Fudong Wang; Xunlin Yang; Yan Yang; Lijuan Sha; et al. (Chemical Geology, 2026)

Retraction notice to “Biochar for urban agriculture: Impacts on soil chemical characteristics and on Brassica rapa growth, nutrient content and metabolism over multiple growth cycles” [Sci. Total Environ. 727 (2020) 138742] - Shuang Song; Srishti Arora; Anna Karen C. Laserna; Ye Shen; Brian W.Y. Thian; Jia Chin Cheong; Jonathan K.N. Tan; Zhongyu Chiam; Siew Lee Fong; Subhadip Ghosh; Yong Sik Ok; Sam F.Y. Li; et al. (Science of The Total Environment, 2026)

Semi-industrial-scale detoxification of cyanide tailings by suspension oxidation roasting and feasibility evaluation for underground backfilling - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Elucidating the oxidation mechanism of phospholipid-based marine oils during storage: A new insight based on the analysis of oxidized phospholipids - Nan Meng; Peixu Cong; Xincen Wang; Yu Song; Yanjun Liu; Yaru Li; Jie Xu; Changhu Xue (Food Research International, 2026)

Investigating the molecular mechanism of plasmalogen and quality changes in Pacific oyster (Crassostrea gigas) depurated under salinity stress - Yu Song; Lili Hao; Xincen Wang; Peixu Cong; Yanjun Liu; Xiaoxu Wang; Zhaojie Li; Changhu Xue; Jie Xu (Food Research International, 2026)

Intensifying ocean stratification reduces vertical phosphate supply and carbon sink magnitude - Rui Wang; Xuegang Li; Jinming Song; Zhibo Wang; Shanshan Liu; Guorong Zhong; Yanjun Wang; Jun Ma; Huamao Yuan; Liqin Duan (Limnology and Oceanography, 2026)
In recent decades, global warming‐driven ocean stratification has profoundly affected nutrient cycling. As the largest marginal sea in the northwestern Pacific, the South China Sea (SCS) provides a representative setting to examine these responses. Based on two decades of temperature, salinity, and nutrient datasets, we quantified the evolution of stratification in the SCS, its impacts on the upward transport of deep‐water phosphate (PO 4 3− ), and the resulting changes in carbon sink. Results show an increasing intensification of stratification, with an upward shift of the thermocline's upper boundary, a downward shift of its lower boundary, increased thickness, and weakened vertical mixing. Despite enhanced external inputs from rivers and atmospheric deposition and reduced phytoplankton consumption of PO 4 3− in the mixed layer, PO 4 3− concentrations have declined persistently, indicating a substantial reduction in nutrient flux from the deep water across the thermocline into the surface layer. The minimum net reduction of PO 4 3− in the upper water column (mixed layer plus thermocline) was −0.047 Gmol·yr −1 . This decline in PO 4 3− supply constrained primary production and reduced CO 2 uptake, leading to an estimated carbon sink reduction of 2.21 × 10 5 t CO 2 ·yr −1 in the SCS.

Simultaneous cyanide detoxification and sulfur immobilization in low-sulfur cyanide tailings via sustainable oxidation roasting: process optimization and mechanistic insights - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Waste Management, 2026)

Operational threshold and associated mechanisms in composting remediation of diesel-contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Environmental Management, 2026)

A novel biogas liquefaction process adopting dual nitrogen expansion cycle with carbon dioxide pre-cooling - Yanjun Huang; Qingfeng Jiang; Xiaofei Lu; Xiao Song; Jiangchao Wang; Huaibin Li (International Journal of Refrigeration, 2026)

Liposome-encapsulated egg yolk immunoglobulin (IgY) enhances anti-Helicobacter pylori efficacy by alleviating gastric inflammation, oxidative stress, and regulating gut microbiota - Peixin Song; Zhishuo Zhang; Ruyi Zhang; Wei Hu; Shengqi Rao; Yanjun Yang; Cuihua Chang (Food Bioscience, 2026)

EPA-rich plasmalogen from Cucumaria frondosa enhances lipophagy by restoring lysosomal acidity via V-ATPase modulation - Zhigao Wang; Xiaoxu Wang; Xincen Wang; Yanjun Liu; Yu Song; Changhu Xue; Jie Xu (Food Bioscience, 2026)

Redox-active co-pyrolytic carbon enhances electron transfer and mitigates petroleum hydrocarbon hazards in contaminated soils - Chengze Yu; Haipeng Huang; Ran Song; Jiaqi Hou; Huibin Du; Mingxiao Li; Yanjun Xin; Beidou Xi (Journal of Hazardous Materials, 2026)

Insight into the mechanism of natural preservatives (rosmarinic acid and phytic acid) against quality deterioration of Pacific white shrimp through interactions with hemocyanin - Junpeng Zeng; Xiaowei Fan; Junyi Song; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Prediction Method and Application of Dynamic Surface Subsidence in Deep-Buried Thick Alluvium Considering Aquifer Consolidation - Shenyi Zhang; Shanxi Wu; Han Zhang; Weijie Wei; Boyuan Cheng; Yanjun Song; Xiujuan Li; Yaochen Wang (Rock Mechanics and Rock Engineering, 2026)

Evolution of non-colinear fault systems from extension to transtension: Northern Dongying Sag, Bohai Bay Basin, East China - Meng Zhang; Kuihua Zhang; Shuang Song; Yanjun Cheng; Zhiping Wu (Journal of Asian Earth Sciences, 2026)

Parameter identification of nonlinear flow characteristics of elongated throttle valve ports in deep-sea hydraulic systems using AD-LHS-SQP - Zekai Wang; Fagang Bai; Xuening Song; Huaqiang You; Yanjun Liu; Gang Xue (Ocean Engineering, 2026)

Unraveling the flavor evolution mechanism in liquid-smoked rainbow trout through integrated lipidomics and flavoromics - Junpeng Zeng; Nan Meng; Xiaowei Fan; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Intermittent blue light-dark cycles: A new strategy for enhancing triterpenoid production in medicinal Sanghuangporus vaninii - Yanjun Ma; Rong Li; Jiahui Li; Zilu Song; Fawen She; Xiaoyan Ma; Xuetai Zhu (Journal of Photochemistry and Photobiology B: Biology, 2026)

A novel compact magnetic quad-stable mechanism for efficiency improvement in point absorber wave energy converters - Xuening Song; Jian Qin; Zekai Wang; Fagang Bai; Lilei Li; Yanjun Liu; Gang Xue (Ocean Engineering, 2025)

Multi-quality attributes prediction and process parameter optimization of liquid-smoked rainbow trout by different machine learning models combined with genetic algorithm - Junpeng Zeng; Jingyi Luo; Yu Song; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Research International, 2025)

Effects of apoptosis on quality changes of Larimichthys crocea postmortem storage with emphasis on cytochrome c-mediated lipid deterioration - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Research International, 2025)

Investigation into the feasibility of cyclone with underflow and bypass flow for improving the performance of circulating fluidized beds - Yuanbo Zheng; Tao Song; Long Ni; Yanjun Xie (Chemical Engineering Journal, 2025)

Lactobacillus acidophilus alleviates polysorbate-80-induced colitis through regulating intestinal microbiota and inhibiting indoleamine 2,3-dioxygenase 1 - Haibin Guan; Xinyuan Tian; Menghe Liu; Yanjun Yue; Jing He; Jianxia Gao; Song You (Archives of Microbiology, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Port Resilience Assessment for Misdeclaration Induced Disasters Using a Hybrid LLM-GNN Framework - Bo Song; Yanjun Weng; Laiqun Xia (Journal of Marine Science and Engineering, 2025)
Ports face critical security threats from hazardous cargo misdeclaration, which poses unique challenges due to its high concealment and catastrophic potential, as exemplified by the Beirut Port explosion. Traditional resilience assessment approaches relying on hazard state transition probabilities require abundant historical data or extensive domain expertise for probability elicitation, and static indicator-based assessment frameworks fail to capture the spatiotemporal evolution characteristics of disasters. To address these challenges, this study proposes a hybrid framework that leverages the Large Language Model (LLM)’s generalizable world knowledge for data augmentation while developing a Spatiotemporal Graph Neural Network (STGNN) to predict dynamic disaster propagation. Specifically, a multimodal LLM is employed to extract structured port state descriptions from temporally aligned disaster data and infer the states at undocumented time steps. With more disaster scenarios adapted from the real cases using the LLM, a STGNN is trained to learn the disaster evolution dynamics and make efficient real-time inference for resilience assessment and intervention strategy evaluation. Validation on Tianjin and Beirut Port incidents demonstrates that the framework accurately predicts disaster propagation pathways and identifies critical intervention priorities. It also reveals that topology-based intervention strategies substantially accelerate recovery, while adverse environmental conditions significantly amplify cumulative functional loss. This study represents an advancement toward AI-driven resilience modeling, offering port operators and regulators an adaptable, scalable decision support tool for intelligent safety governance.

Promising mass spectrometry imaging: exploring microscale insights in food - Xinyu Cao; Peixu Cong; Yu Song; Yanjun Liu; Changhu Xue; Jie Xu (Critical Reviews in Food Science and Nutrition, 2025)

Waypoint-based path following for robotic fish with hybrid actuators - Fagang Bai; Zekai Wang; Xuening Song; Yanjun Liu; Kexian Liu; Gang Xue (Ocean Engineering, 2025)

Porous Janus membrane for ultrasensitive detection and efficient degradation of sulfur mustard simulant - Meiyang Jin; Shuya Liu; Hailong Jiang; Xia Wang; Yongxian Guo; Yanjun Gong; Qiongzheng Hu; Ru-Song Zhao (Journal of Hazardous Materials, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Arsenic exposure, genetic susceptibility, lifestyle, and glucose-insulin homeostasis impairment: Revealing the association and interaction in a repeated-measures prospective study - Yongfang Zhang; Jiahao Song; Ming Zhang; Gaoyin Xiong; Yanjun Guo; Wei Liu; Linling Yu; Quanhong Liu; Yueru Yang; Shuhui Wan; Qing Liu; Zhiying Huo; et al. (Environmental Research, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Effects of Dish-Shaped Buoy and Perforated Damping Plate on Power Absorption in Floating Two-Body Wave Energy Converters - Lilei Li; Changdong Wei; Mingchen Li; Xuening Song; Yanjun Liu; Gang Xue (Journal of Marine Science and Engineering, 2025)
Floating two-body wave energy converters (WECs) exhibit advantages, including insensitivity to water depth and tidal range, along with adaptability to multi-level sea states. However, WECs suffer from drawbacks, including unstable power generation and low wave energy capture efficiency. To enhance the hydrodynamic performance and energy capture efficiency, a dish-shaped buoy and perforated damping plate configuration was designed based on conventional two-body WECs. First, four two-body WECs were developed according to these configurations. Second, a numerical model based on potential flow theory and the boundary element method (BEM) was established, with its accuracy validated through sea trials. Finally, the frequency domain response, motion response, mooring tension and power absorption effect of the WECs under wave excitation of grades 3, 4 and 5 were analyzed. The results demonstrate that both the dish-shaped buoy and perforated damping plate significantly improve the device stability and energy capture potential. Regarding the motion response, both configurations reduced the peak response amplitudes in heave and roll, enhancing the device stability. For mooring tension, both configurations reduced the mooring line tension. For power absorption, the perforated damping plate effectively increased the energy capture efficiency, while the dish-shaped buoy also demonstrated superior performance under higher-energy wave conditions. Overall, this study provides a theoretical foundation and design guidance for floating two-body WECs.

The hominin teeth from the late Middle Pleistocene Hualongdong site, China - Xiujie Wu; María Martinón-Torres; Song Xing; Shuwen Pei; Yanjun Cai; Haowen Tong; José María Bermúdez de Castro; Wu Liu (Journal of Human Evolution, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Salting-induced lipid hydrolysis and oxidation in dried squid fillets: A mechanistic link to formaldehyde formation, color browning, and flavor alteration - Junpeng Zeng; Xiaowei Fan; Nan Meng; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Research on design, modeling, and maneuverability analysis of hybrid-driven robotic fish - Fagang Bai; Xuening Song; Zekai Wang; Xingyao Wang; Yanjun Liu; Kun Liu; Gang Xue (Frontiers in Marine Science, 2025)
Hybrid-driven robotic fish combines the maneuverability of propeller propulsion with the efficiency of biomimetic fin propulsion, offering potential advantages in underwater exploration and robotic applications. This paper presents the design and development of a hybrid-driven robotic fish that integrates both biomimetic fin and propeller propulsion systems. Initially, the kinematic and dynamic modeling challenges associated with robotic fish are addressed, establishing a comprehensive coupled mathematical model that accounts for the robotic fish’s six degrees of freedom and the actuator dynamics. Subsequently, computational fluid dynamics techniques are employed to simulate a virtual tank for the robotic fish, and hydrodynamic data fitting is performed to determine key parameters such as damping coefficients and thrust coefficients. Finally, a simulation platform based on MATLAB/Simulink is constructed to simulate the robot’s motion, validated through comparisons with simulated calculations and experimental observations. Based on these findings, this paper further analyzes the robotic fish’s maneuverability metrics, including its surge speed, turning radius, and motion characteristics in three-dimensional space, and examines how perturbations in hydrodynamic coefficients affect swimming speed. This study provides valuable insights into the complex motion modeling and performance prediction of hybrid-driven robotic fish, and establishes a foundation for future studies on the motion control of robotic fish.

Improved assessment of post-fire recovery trajectory of forests in Amazon's protected areas - Qianhan Wu; Calvin K.F. Lee; Jonathan A. Wang; Yingyi Zhao; Guangqin Song; Eduardo Eiji Maeda; Yanjun Su; Alfredo Huete; Alice C. Hughes; Jin Wu (Remote Sensing of Environment, 2025)

Insights to enhanced coagulation based on the control of metal forms for treating acid mine drainage: Performance and mechanisms - Kun Wu; Yanjun Jia; Dandan Song; Angzhen Li; Xue Bai; Xuan Sun; Rongle Li; Zhihua Li (Journal of Hazardous Materials, 2025)

MiR-30d-5p Modulates Glucose and Lipid Metabolism by Targeting CD73 through the AMPK Pathway - Mingjie Song; Juan Wang; Wenli Mu; Yanwei Zheng; Yanjun Cai; Jing Liu; Yu Xia (Cell Biochemistry and Biophysics, 2025)

Metamorphic evolution and tectonic significance of garnet-bearing amphibolites from the upper valley of the Hatu River, East Kunlun Orogenic Belt - Xiaohui Liu; Zeng Lü; Zhenyu Chen; Shuguang Song; Yanjun Guo (Lithos, 2025)

Fabrication of TiO2/CuFeO2 composites for oxytetracycline degradation through heterogeneous photo-Fenton-like process under visible light - Xue Li; Jinying Li; Jiaying Song; Zhiying Li; Xicheng Yuan; Lingyun Meng; Wenzhuo Xu; Qianwen Wang; Qinghua Yan; Shuaishuai Xin; Chengzhi Zhou; Guocheng Liu; et al. (Journal of Environmental Management, 2025)

Preparation, identification and application of lipid-Maillard reaction products during the drying process of squid fillets - Junpeng Zeng; Xiaowei Fan; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Multi-scale coupling measurement and driving factor analysis between carbon emission from energy consumption and ecological environment—The case study of Pearl River Delta urban agglomeration - Yanjun Wang; Mengru Song; Yongshun Han; Yichang Wang (Sustainable Cities and Society, 2025)

The new insight into the impact of hemocyanin on quality deterioration of Pacific white shrimp during refrigerated storage - Xiaowei Fan; Junyi Song; Yu Song; Yanjun Liu; Junpeng Zeng; Jie Xu; Changhu Xue (Food Chemistry, 2025)

The catalytic activity of Ca/Fe-rich incineration ash in the pyrolysis of epidemic wood - Yanjun Hu; Zhenxing Luo; Long Jiao; Caimeng Yu; Jian Li; Qianqian Guo; Jian Song (Waste Disposal & Sustainable Energy, 2025)

Single-B-cell cloning and recombinant antibodies generation to analyze the antigenicity of porcine reproductive and respiratory syndrome virus nonstructural protein 12 - Hongyong Duan; Chaozhi Tang; Song Han; Nan Yang; Shumao Wang; Fei Gao; Yanjun Zhou; Guangzhi Tong; Kuan Zhao; Liwei Li (Veterinary Microbiology, 2025)

Insights into the enhanced removal of ciprofloxacin by Ni1Mn1Fe1-LDO activated peroxymonosulfate: Mechanism and application for antibiotic wastewater - Siqi Liu; Wenqi Bu; Xiangting Hou; Shixu Lu; Chengzhi Zhou; Xiaozhe Song; Qianwen Wang; Shuaishuai Xin; Guocheng Liu; Yanjun Xin; Qinghua Yan (Process Safety and Environmental Protection, 2025)

Effects of mitochondrial lipidome alterations on quality deterioration of Larimichthys crocea postmortem storage: New insight from the perspective of mediating mitochondria-dependent apoptosis - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Insight into the mechanism of Maillard reaction and lipids mutually contribute to the flavor release of squid fillets during the drying process - Junpeng Zeng; Nan Meng; Yu Song; Xiaowei Fan; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2025)

Impacts of high-methoxyl pectin on structure, composition, and rheological properties of milk fat globule emulsion - Yanjun Sun; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2025)

Lipid-involved browning mechanism during the drying process of squid - Junpeng Zeng; Yu Song; Xiaowei Fan; Yanjun Liu; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Mechanisms by which Ganglioside GM1, a specific type of glycosphingolipid, ameliorates BMAA-induced neurotoxicity in early-life stage of zebrafish embryos - Yanjun Liu; Yuhe Zhu; Xiaoxu Wang; Yiyang Li; Shuaiqi Yang; Hongyan Li; Bo Dong; Zhigao Wang; Yu Song; Jie Xu; Changhu Xue (Food Research International, 2025)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Visible-light-driven photobiocatalytic synthesis of chiral sulfoxides over immobilized chloroperoxidase on magnetic yolk–shell Fe3O4@Cu-H-TiO2 photocatalyst - Xiaoyang Yue; Yuying Hou; Cuiyao Cao; Xue Cao; Haolei Song; Yanjun Jiang; Liya Zhou; Ying He; Xiaobing Zheng; Li Ma; Shijie Li (Journal of Cleaner Production, 2024)

Effect of cytochrome c release on the mitochondrial-dependent apoptosis and quality deterioration of black rockfish (Sebastes schlegelii) postmortem storage - Xiaowei Fan; Yu Song; Yanjun Liu; Junyi Song; Junpeng Zeng; Zhaojie Li; Jie Xu; Changhu Xue (Food Chemistry, 2024)

Characterization of the microstructure, interfacial properties and crystallization behaviours of milk fat globule and membrane isolated from acidified bovine milk and sweet whey - Yanjun Sun; Yrjö H. Roos; Song Miao (Food Hydrocolloids, 2024)

Mechanochromic luminescent material with high quantum yield for multi-mode anti-counterfeiting applications - Yongxian Guo; Aoli Wu; Qiaoru Zhang; Mei Zhao; Yanjun Gong; Shuya Liu; Mashooq Khan; Haoyang Song; Juyoung Yoon; Qiongzheng Hu (Chemical Engineering Journal, 2024)

A review of factors affecting the structure, compositions, and the techno-functionalities of bovine milk fat globule and membrane - Yanjun Sun; Yrjö H. Roos; Song Miao (Trends in Food Science & Technology, 2024)

Highly efficient peroxymonosulfate activation by CoFe2O4@attapulgite–biochar composites: Degradation properties and mechanism insights - Yanjun Pan; Fanyue Meng; Jixing Bai; Bing Song; Qi Cao (Journal of Environmental Chemical Engineering, 2024)

Design and Performance Evaluation of an Enclosed Inertial Wave Energy Converter with a Nonlinear Stiffness Mechanism - Jian Qin; Zhenquan Zhang; Xuening Song; Shuting Huang; Yanjun Liu; Gang Xue (Journal of Marine Science and Engineering, 2024)
In order to enhance the power generation efficiency and reliability of wave energy converters (WECs), an enclosed inertial WEC with a magnetic nonlinear stiffness mechanism (nonlinear EIWEC) is proposed in this paper. A mathematical model of the nonlinear EIWEC was established based on the Cummins equation and the equivalent magnetic charge method, and the joint simulations were carried out using MATLAB/Simulink 2020 and AMESim 2020 softwares. The effect of the magnetic nonlinear stiffness mechanism (NSM) on the performance of the EIWEC system was investigated. The results show that the nonlinear negative stiffness property of NSM can significantly improve the motion response and output power of EIWEC under low-frequency waves. Compared to EIWEC without NSM (linear EIWEC), nonlinear EIWEC has a higher generation efficiency and wider frequency bandwidth. Additionally, the effects of linear spring, internal mass body, and hydraulic power take-off (PTO) system parameters on the energy conversion capability of the system were analyzed to provide a reference for the design of nonlinear EIWECs. In general, the proposed nonlinear EIWEC could provide good development potential for the scale utilization of wave energy resources.

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Obtention, interaction, and characterization of the soy protein isolate-glycyrrhizin nanocomplex for encapsulating naringenin - Qingchen Cui; Xixi Song; Mengshuang Li; Yanjun Wei; Juan Dong; Xianggen Wu (Food Hydrocolloids, 2023)

Identification of Fangchinoline as a novel autophagy inhibitor with an adjuvant of chemotherapy against lung cancer - Zhenyang Ren; Yue Song; Jinhuan Xian; Yuan Liao; Yujuan Zhan; Tingxiu Zhao; Huiqi Wang; Junbo Jiang; Mansi Xu; Yanjun Jiang; Xiaodong Liu; Xianli Wei; et al. (Toxicology and Applied Pharmacology, 2023)

Flame retardant and multifunctional BC/MXene/MSiCnw/FRTPU aerogel composites with superior electromagnetic interference shielding via “Consolidating” method - Hengrui Wang; Kexin Chen; Yongqian Shi; Yanjun Zhu; Songqiong Jiang; Yan Liu; Shijie Wu; Chenxin Nie; Libi Fu; Yuezhan Feng; Pingan Song (Chemical Engineering Journal, 2023)

Highly efficient nanocomposite of Y2O3@biochar for oxytetracycline removal from solution: Adsorption characteristics and mechanisms - Jiaying Song; Lun Lu; Jian Wang; Xue Li; Jinying Li; Qianwen Wang; Haiyan Du; Shuaishuai Xin; Lina Xu; Qinghua Yan; Chengzhi Zhou; Guocheng Liu; et al. (Bioresource Technology, 2023)

Adsorption Characteristics and Mechanisms of Oxytetracycline on Nano Biochar: Effects of Environmental Conditions and Particle Aggregation - Wenqiang Jia; Xiangrui Pan; Jiaying Song; Jian Wang; Weikai Sun; Yanjun Xin; Qinghua Yan; Chengzhi Zhou; Hao Zheng; Guocheng Liu (Water, Air, & Soil Pollution, 2023)

Fenton oxidation treatment of oxytetracycline fermentation residues: Harmless performance and bioresource properties - Wenqiang Jia; Jiaying Song; Jian Wang; Jinying Li; Xue Li; Qianwen Wang; Xiang Chen; Guocheng Liu; Qinghua Yan; Chengzhi Zhou; Shuaishuai Xin; Yanjun Xin (Chemosphere, 2023)

Morphological and morphometric analyses of a late Middle Pleistocene hominin mandible from Hualongdong, China - Xiujie Wu; Shuwen Pei; Yanjun Cai; Haowen Tong; Ziliang Zhang; Yi Yan; Song Xing; María Martinón-Torres; José María Bermúdez de Castro; Wu Liu (Journal of Human Evolution, 2023)

Gene-environment interaction in long-term effects of polychlorinated biphenyls exposure on glucose homeostasis and type 2 diabetes: The modifying effects of genetic risk and lifestyle - Qiyou Tan; Shijie Yang; Bin Wang; Mengyi Wang; Linling Yu; Ruyi Liang; Wei Liu; Jiahao Song; Yanjun Guo; Min Zhou; Weihong Chen (Journal of Hazardous Materials, 2023)

Mapping foliar photosynthetic capacity in sub-tropical and tropical forests with UAS-based imaging spectroscopy: Scaling from leaf to canopy - Shuwen Liu; Zhengbing Yan; Zhihui Wang; Shawn Serbin; Marco Visser; Yuan Zeng; Youngryel Ryu; Yanjun Su; Zhengfei Guo; Guangqin Song; Qianhan Wu; He Zhang; et al. (Remote Sensing of Environment, 2023)

High performance and mechanism of Tl(I) removal from solution by synergetic application of nanowire γ-MnOOH@biochar and free radicals: Implications to AMD treatment - Jin Wang; Shan Yu; Yanjun Jiang; Yanyi Liu; Xinni Xiong; Jun Xiao; Mengqing Sun; Jingzi Beiyuan; Juan Liu; Gang Song (Journal of Water Process Engineering, 2023)

ROS-activated selective fluorescence imaging of cancer cells via the typical LDH-based nanozyme - Zhengdi Wang; Jiancheng Liu; Min Feng; Kai Song; Kaitao Li; Wendi Liu; Shanyue Guan; Yanjun Lin (Chemical Engineering Journal, 2023)

Cyanide detoxification and iron mineral recycle of cyanide tailings by the sustainable utilization technology of oxidation-reduction roasting: Process optimization and mechanism study - Bing Zhao; Lingbo Zhao; Peng Gao; Yuexin Han; Yanjun Li; Zaizheng Dong; Yan Song (Journal of Environmental Chemical Engineering, 2023)

Lipidomics approach in alcoholic liver disease mice with sphingolipid metabolism disorder: Alleviation using sea cucumber phospholipids - Zhigao Wang; Xiaoxu Wang; Yuliu Wang; Yanjun Liu; Xincen Wang; Yu Song; Jie Xu; Changhu Xue (Food Bioscience, 2023)

Meeting the heavy-metal safety requirements for food crops by using biochar: An investigation using sunflower as a representative plant under different atmospheric CO2 concentrations - Yiying Wang; Guiying Lin; Xian Li; Ming Hang Tai; Shuang Song; Hugh Tiang Wah Tan; Ken Leong; Elvis Yew Boon Yip; Grace Yoke Chin Lee; Yanjun Dai; Chi-Hwa Wang (Science of The Total Environment, 2023)

Effects of amino acids on the formation and distribution of glycerol core aldehydes during deep frying - Jianhua Huang; Lijun Wang; Yanjun Guo; Chuying Chen; Zhihua Song; Xingguo Wang (Food Research International, 2023)

The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Guorong Zhong; Xuegang Li; Jinming Song; Baoxiao Qu; Fan Wang; Yanjun Wang; Bin Zhang; Detong Tian; Jun Ma; Huamao Yuan; Liqin Duan; Ning Li; et al. (Frontiers in Marine Science, 2022)
The Pacific Ocean is one of the important carbon sink regions, and there is a significant west-east difference in sea-air CO 2 flux. However, the influence of the long-standing greater CO 2 uptakes in the western Pacific than in the east and the dynamic change of this west-east difference remain unclear. In this paper, using the gridded surface ocean p CO 2 product constructed by the stepwise FFNN algorithm, we reported an increasing west-east CO 2 flux difference from 0.41 PgC yr -1 in 1992 to 0.73 PgC yr -1 in 2020. This increase was mainly attributed to the strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source. During El Nino events, the west-east CO 2 flux difference decreased significantly in a few years, and it then rose back rapidly when El Nino events ended. In addition, the increasing west-east difference in CO 2 uptakes during the last three decades did not lead to a higher acidification speed in the western surface temperate Pacific than the east. The greater CO 2 absorbed in the west was mainly transported to the deeper waters and caused a more significant carbon inventory change at 200-600 m than the eastern Pacific.

Temporal genetic variation of the Chinese longsnout catfish (Leiocassis longirostris) in the upper Yangtze River with resource decline - Yanjun Jin; Kun He; Peng Xiang; Xiaodong Wang; Lintian Tong; Zhen Wei; Xiuyue Zhang; Zhaobin Song (Environmental Biology of Fishes, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Dynamic physiological and transcriptome changes reveal a potential relationship between the circadian clock and salt stress response in Ulmus pumila - Panfei Chen; Peng Liu; Quanfeng Zhang; Lei Zhao; Xuri Hao; Lei Liu; Chenhao Bu; Yanjun Pan; Deqiang Zhang; Yuepeng Song (Molecular Genetics and Genomics, 2022)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Mechanical Properties of Acid-corroded Sandstone Under Uniaxial Compression - Shuguang Li; Yingming Wu; Runke Huo; Zhanping Song; Yoshiaki Fujii; Yanjun Shen (Rock Mechanics and Rock Engineering, 2021)

Spatial–temporal differences in disaster perception and response among new media users and the influence factors: a case study of the Shouguang Flood in Shandong province - Shuolin Geng; Qi Zhou; Mingjie Li; Dianxing Song; Yanjun Wen (Natural Hazards, 2021)

mRNA and microRNA Profiles in the Amygdala Are Relevant to Susceptibility and Resilience to Psychological Stress Induced in Mice - Jinyan Sun; Yanjun Lu; Jiuyong Yang; Zhenhua Song; Wei Lu; Jin-Hui Wang (Journal of Molecular Neuroscience, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Method validation, storage stability and field trial for residues of florasulam and pyroxsulam in cereal by liquid chromatography with tandem mass spectrometry - Yingying Bi; Lijun Han; Shuangyu Song; Wei Yao; Fayi Qin; Yanjun Xu; Qiong Wu (Food Additives & Contaminants: Part A, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Permeability dynamic variation of coal under various confining pressures using LFNMR relaxation method - Peng Xia; Fangui Zeng; Xiaoxia Song; Beilei Sun; Taotao Yan; Wei Li; Yanjun Meng (Arabian Journal of Geosciences, 2020)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

Characteristics of dry-wet abrupt alternation events in the middle and lower reaches of the Yangtze River Basin and the relationship with ENSO - Lijie Shan; Liping Zhang; Jiyun Song; Yanjun Zhang; Dunxian She; Jun Xia (Journal of Geographical Sciences, 2018)

Pharmacokinetics and immunogenicity of T0001, a newly developed anti-TNFα fusion protein, in healthy volunteers - Yitong Wang; Chang Liu; Shi Chen; Wei Wang; Lihou Dong; Qian Wang; Yan Wang; Libo Zhao; Yannan Zang; Zhenwei Xie; Yang Liu; Yanjun Liu; et al. (European Journal of Clinical Pharmacology, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Structural block division for further deep research in coalbed methane development in the Gujiao area, Xishan coalfield, North China - Peng Xia; Fangui Zeng; Xiaoxia Song; Yanjun Meng; Kunjie Li; Jin Wang; Beilei Sun (Arabian Journal of Geosciences, 2016)

Risk factors of severe hand, foot and mouth disease complicated with cardiopulmonary collapse - Chunlan Song; Cheng Yibing; Yanjun Guo; Zhipeng Jin; Yajie Cui; Xue Gu (Infectious Diseases, 2015)

Identification of key nitrous oxide production pathways in aerobic partial nitrifying granules - Satoshi Ishii; Yanjun Song; Lashitha Rathnayake; Azzaya Tumendelger; Hisashi Satoh; Sakae Toyoda; Naohiro Yoshida; Satoshi Okabe (Environmental Microbiology, 2014)
Summary The identification of the key nitrous oxide ( N 2 O ) production pathways is important to establish a strategy to mitigate N 2 O emission. In this study, we combined real‐time gas‐monitoring analysis, 15 N stable isotope analysis, denitrification functional gene transcriptome analysis and microscale N 2 O concentration measurements to identify the main N 2 O producers in a partial nitrification ( PN ) aerobic granule reactor, which was fed with ammonium and acetate. Our results suggest that heterotrophic denitrification was the main contributor to N 2 O production in our PN aerobic granule reactor. The heterotrophic denitrifiers were probably related to R hodocyclales bacteria, although different types of bacteria were active in the initial and latter stages of the PN reaction cycles, most likely in response to the presence of acetate. Hydroxylamine oxidation and nitrifier denitrification occurred, but their contribution to N 2 O emission was relatively small (20–30%) compared with heterotrophic denitrification. Our approach can be useful to quantitatively examine the relative contributions of the three pathways (hydroxylamine oxidation, nitrifier denitrification and heterotrophic denitrification) to N 2 O emission in mixed microbial populations.

Analysis of molecular variation of porcine reproductive and respiratory syndrome virus in Central China from 2006 to 2012 - Yuejun Shi; Zhibin Hu; Zhenghui Xiong; Yanjun Zhou; Xin Jin; Changqin Gu; Xueying Hu; Guofu Cheng; Nianhua Song; Wanpo Zhang (Archives of Virology, 2013)

Long-Term Heavy Metal Pollution and Mortality in a Chinese Population: An Ecologic Study - Mao Wang; Yanjun Xu; Shangxia Pan; Jinxin Zhang; Aiming Zhong; Hong Song; Wenhua Ling (Biological Trace Element Research, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)